KERUSAKAN LINGKUNGAN AKIBAT PEMBANGUNAN INFRASTRUKTUR - Tri Habil Adha; Irwan Irwan (Universitas Negeri Padang, 2021)
The purpose of making this final work of graphic art is to visualize forms of environmental damage due to infrastructure development with serigraphy techniques and also to create working techniques in graphic arts and to deepen the concept of work. The stages used in this final work are the stages of preparation, elaboration, synthesis, concept realization and completion stages. So that ten works were created that visualize the form of environmental damage due to infrastructure development with the following titles: the first work is